Implementation of Discussion Method to Increase Student Activeness in Islamic Education Learning at SD Negeri 081228 Sibolga - Wati, Linda; Siregar, Pida Satriani; Simamora, Merlina (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve student activity in Islamic education learning by using discution method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data of this study were obtained by test and observation techniques. The test is used to measure student activity in Islamic education learning and observation is used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that discution method can improve student activity in Islamic education learning. This can be seen from the increase in the percentage of student activity completion in each cycle with details of the pre-cycle 46.56%, the first cycle 68.47% and in the second cycle increased to 90.57%. Thus, the use of discution method can be used as an alternative to improve student activity in Islamic education learning in Islamic education learning.